Las Ferias de Ciencia y Tecnología de Costa Rica y sus aportes a la educación secundaria - Retana Alvarado, Diego Armando; Vázquez Bernal, Bartolomé; Camacho Álvarez, María Marta (Universidad de Costa Rica, 2018)
This article analyzes the contributions of Science and Technology Fairs in the promotion of scientific and technological vocations in Secondary Education among students whose research projects were selected to participate in the National Science and Technology Fair of Costa Rica in 2010 to 2013. It identifies the components that motivate the decisions of preference and choice of higher scientific-technological studies in high school students, as well as the identification of teachers’ actions and aspects to be redefined for the effective promotion. From a mixed design of concurrent triangulation, 45 students and 17 teachers were surveyed. The results emphasize the development of scientific competencies, the promotion of favorable attitudes, the approach to the scientific work, the teaching and learning processes and the judging as motivating components in the choice of studies in those areas. Such influence was evident in a higher preference for technological careers and scientific studies at the time they first start university. Science teachers encourage students to carry out research projects and provide the accompaniment during its development and presentation in all stages. From the National Science and Technology Fairs Program, it is necessary the training of active teachers and the revision of the current pedagogical and organizational model